2022
DOI: 10.3390/land11122331
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Permafrost Conditions along Pipeline Routes in Central Yakutia, Russia

Abstract: Pipelines are critical infrastructure for Yakutia, transporting vital supplies to communities in this vast northern region. The pipeline routes in central Yakutia traverse areas of ice-rich permafrost that is sensitive to temperature changes. This study examined the thermal state of permafrost in undisturbed and disturbed settings along the Lena River to Mundulakh Reservoir water pipeline and the Mastakh to Yakutsk gas pipeline and considered the effects of climatic fluctuations and surface disturbances (fores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…It can be shown that the electric field strength obtained under similar conditions is the fundamental solution in time to problem ( 21)- (25). Accordingly, its Sumudu image in time satisfies (19) and (20). If the radii of the loops are sufficiently small compared to the distance between their centers, then the transmitter loop can be replaced with a vertical magnetic dipole; the EMF in the receiver coil can be taken to be proportional to the time derivative of the z-component of the magnetic field strength…”
Section: Computational Experimentsmentioning
confidence: 92%
See 2 more Smart Citations
“…It can be shown that the electric field strength obtained under similar conditions is the fundamental solution in time to problem ( 21)- (25). Accordingly, its Sumudu image in time satisfies (19) and (20). If the radii of the loops are sufficiently small compared to the distance between their centers, then the transmitter loop can be replaced with a vertical magnetic dipole; the EMF in the receiver coil can be taken to be proportional to the time derivative of the z-component of the magnetic field strength…”
Section: Computational Experimentsmentioning
confidence: 92%
“…We assume the current density in the loop J 0 (u) to be constant. Then, the right-hand side of (19) will correspond (up to sign) to the Sumudu image of the δ-function, which is equivalent to the stepwise switching on of the current at time t = 0. Thus, the solution to the boundary-value problem ( 19)- (20) will be the Sumudu image of the fundamental solution to problem ( 21)- (24) in time.…”
Section: Modeling Tem Signals Through Sumudu Transformmentioning
confidence: 99%
See 1 more Smart Citation